PENGARUH PERAN DEWAN PENGAWAS SYARIAH (DPS) DAN KOMITE AUDIT TERHADAP KEPATUHAN PADA PRINSIP SYARIAH - Hikmah, Liatul; Oktaviana, Ulfi Kartika (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2019)
Sharia Supervisory Board (DPS) and Audit CommitteeÂ  are company organ for Responbility implementation of sharia Compliance in Sharia Community Financing Banks (BPRS). The purpose of this research was to test the role of Sharia Supervisory Board (DPS) and Audit Committee effects on compliance with sharia principles in Sharia Community Financing Bank (BPRS) in East Java.The research population was all BPRS of East Java Province which are registered in the Financial Service Authority (OJK) and Bank Indonesia (BI). The sample size was 15 institutions which were taken using purposive sampling method. Data collection method used approximation quantitative method withÂ  questionnaires with total 0f 38 questionnaires returned. This research used Data analysis multiple linear regression test with SPSS 16. The research variables include 19 indicators of DPS supervision activities, 7 indicators of Audit Committee responsibilities and 12 indicators of Shariah Compliance indicators.The results revealed that the role of Sharia Supervisory Board (DPS) partially had a negative effect. Its mean Shariah Complience in BPRS East Java has not been fully influenced role of DPS because DPS rarely visited to BPRS and certification levels are still low. While the role of the Audit Committee has a positive effect on Sharia compliance in the BPRS East Java. Simultaneously, the role of Sharia Supervisory Board (DPS) and Audit Committee had an effect on compliance with sharia principles in BPRS East Java. According to the dominant variables revealed that the role of Audit Committee is more influential on Compliance with Sharia Principles in BPRS East Java compared to the role of Sharia Supervisory Board (DPS ).Â